Interpretasi Al-Qur’an terhadap Feminisme dan Gender pada QS. Ali Imran Ayat 195 dalam Perspektif Tafsir Tahlili - Fauzi, Hakimul; Mudawwamah, Hasanah Lillah; Effendy, M Fikrie Maulana Akbar (Jurnal Riset Agama, 2024)
The discussion in this article brings up the issue of feminism and gender. This topic is then analyzed through the interpretation of Qur'anic verses. Feminism itself is a movement that demands equal rights between men and women and eliminates gender discrimination in society. The type of research used is qualitative research presented with descriptive-analytical method. This research uses an analytical review (tafsir tahlili) that focuses on one of the Qur'anic verses related to feminism and gender, namely QS. Ali Imran verse 195. The results and conclusions of the research show that both the interpretations of classical and contemporary scholars illustrate the complexity of the content of the verse as well as the agreement on the value that is the basis of feminism and gender issues, namely the value of justice.